PENGEMBANGAN MEDIA KOMIK MELALUI APLIKASI FACEBOOK PADA MATA PELAJARAN BAHASA INDONESIA KELAS V MIS MIFTAHUL JANNAH TAHUN PEMBELAJARAN 2025-2026 - Apriyana, Nana; Rosmawati Harahap; Ahmad Landong; Sujarwo, Sujarwo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
For this study, we will create a comic book using a Facebook application for teachers in Indonesia to use with their students. The purpose of this assessment is to determine the usability, effectiveness, and practicality of this media for fifth-grade students at MIS Miftahul Jannah. The research and development followed the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. A total of 25 fifth-grade students participated in this study. Validation sheets for professional and student surveys were used to obtain data. The results of this study support the idea that classrooms in Indonesia can benefit from the use of Facebook comics. Studies show that fictional comics can change the world for the better. The percentage of validation by media experts increased from 63.33% in the first stage,